2003
DOI: 10.17705/1cais.01116
|View full text |Cite
|
Sign up to set email alerts
|

Management Information Systems Research: What's There in a Methodology?

Abstract: Management information systems (MIS) is both a young and unique field , constantly experiencing rapid change and turmoil. Consequently, MIS research faces dual changes of rigor and relevance. Many research methodologies exist that provide various combinations of rigor and relevance. The MIS researcher selects a methodology based on several factors including rigor, relevance, subject area, and personal preferences. In this article, we examine thirteen different methodologies as used by seven leading MIS journal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
78
1
4

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(85 citation statements)
references
References 29 publications
(36 reference statements)
2
78
1
4
Order By: Relevance
“…Three types of analyses have been reported in the literature when examining past research: research topics and themes [1,6,7,9,18], research methodologies [5,10,12,15,16], productive authors and universities [2,11,14]. In the same vein, this article analyzes publication trends in Information and Management and has a few objectives: 4. to identify the most applied research methodologies and their trends; 5. to identify best practices, by examining the subject areas and methodologies preference of the most productive authors.…”
Section: Introductionmentioning
confidence: 99%
“…Three types of analyses have been reported in the literature when examining past research: research topics and themes [1,6,7,9,18], research methodologies [5,10,12,15,16], productive authors and universities [2,11,14]. In the same vein, this article analyzes publication trends in Information and Management and has a few objectives: 4. to identify the most applied research methodologies and their trends; 5. to identify best practices, by examining the subject areas and methodologies preference of the most productive authors.…”
Section: Introductionmentioning
confidence: 99%
“…The value of scientometrics has been already recognized in MIS (Straub 2006), and numerous projects have been conducted (Vessey et al 2002;Lowry et al 2007) with most analyzing the articles published in a select set of leading journals (Palvia et al 2003(Palvia et al , 2004. Recently, some researchers also started exploring the body of knowledge in conference proceedings (Chan et al 2006;Xu and Chau 2006;McLaren and Mills 2008).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Thus, there seems to be a large body of knowledge geared towards coalescing and informing on the progression of the MIS research in general and specifically survey research techniques. (Palvia et al, 2003) to studies that have sought to investigate whether the research methods used in the MIS field are indicative of the maturation of the field (Culnun and Swanson, 1986). The major motivation of this study is to build on the works shown in Table I through an assessment of the prevalent sources of data, unit of analysis, respondents in the existing MIS survey research articles as well as identifying the prevalent statistical techniques and data analysis tools used in these studies.…”
Section: Introductionmentioning
confidence: 99%
“…However, unlike many prior studies that have broadly addressed aspects of MIS research methodologies (for instance, Farhoomand and Drury, 1999 -investigated MIS research methods and generated a taxonomy of MIS research methodology, or Palvia et al, 2003 -ranked MIS research methodologies), this study specifically seeks to address data collection issues and subsequent analysis in MIS survey-based research. As shown in Table I, there is a wide variation in the study periods as well as the number of journals covered by the review articles with the time spans tending to range from a couple years (Palvia et al, 2003) to a high of 21 years (Alavi and Carlson, 1992). In terms of journal coverage, the current study closely resembles Pinsonneault and Kraemer (1993) whose study covered articles published in 16 core MIS journals while on time span, the current study closely mirrors Alavi and Carlson (1992) whose study covered articles in eight core MIS journals published between 1968 and 1988.…”
Section: Introductionmentioning
confidence: 99%